O ensino médio politécnico no Rio Grande do Sul: politecnia ou polivalência? - Souza, Orides Messias Maia de (Universidade do Vale do Rio dos Sinos, 2016)
This work has as its theme the Polytechnic High School of the State in Rio Grande do Sul, in the context of public policies in education and flexible capital accumulation. In the survey, we make a study of the theoretical basis of the proposal and the practical context, to analyze the formation that occurs in high school today is more in line with the concept of polytechnic or multifunctionality. Thus, we analyze how the polytechnic and multifunctionality interrelate with the proposal and with the practice of public policy in Polytechnic High Scholl, in the context of flexible accumulation of capital, in order to characterize the conceptions of polytechnic All-round and identify the polytechnic occurs in the context of practice. To this end, we conducted a theoretical and empirical study in two schools: E. E. E. M. CAIC Madezatti, located in São Leopoldo/RS, and the Institute for State Education Rubén Darío, located in Sapucaia do Sul/RS; and the State Department of Education, which maintains this area, responsible for the implementation of the Polytechnic proposal to the school environment. We made the choice of these two distinct spaces, understanding that public policies are configured in fact on the school ground, as they are subject to reinterpretations and recreations of the actors involved in implementation; however, the context of equally relevant sponsor in this process because the professionals Seduc also made their reinterpretations, changing often your vision and making changes deemed necessary. We used as a method dialectical historical materialism, in qualitative research, dialoguing with the documents that guide the proposed reform of the MS and works of Antonio Gramsci, Acacia Kuenzer, Dermeval Saviani, Gaudencio Frigotto, Jefferson Mainardi, Paolo Nosella, Ricardo Antunes among others. As instruments of data collection applied semi-structured interviews with school administrators, educational manager (representative Seduc) and teachers of the discipline of Integrated Seminar for analysis of Polytechnic High School and its contradictions related to public policies and training in perspective the polytechnic and / or multifunctionality in the context of practice. We can see the contradictions imposed by capitalism in the implementation of Polytechnic High School, because on the one hand, the restructuring of the MS pointed to an education in the work perspective as an educational principle, with integral human development and providing an inclusive school vision; on the other hand, in the context of practice, the subjects involved ressignificaram the proposal, changing to some extent the central idea, because they live in a society that follows the interests of capitalism, the mercantile and utilitarian logic, who see education as a means of preparation to work and vestibular. We still see that the reform, despite the limitations faced by school and Seduc spaces, obtained some important advances, such as the creation of a research culture in schools. We note that the polytechnic is not taking place in the context of the practice, because it takes time to deconstruct a culture based on the work as exchange value, and build a collective work culture. However, we believe that the restructuring of High School made a way for the education perspective that form from humanitarian principles.
Keywords: Política pública; Ensino médio politécnico; Politecnia; Polivalência; Reforma do ensino médio; Public policy; High school polytechnic; Polytechnic multifunctionality; Reform of high school; ACCNPQ::Ciências Humanas::Educação